A comparison of multiple platforms for quantifying ATN values in cerebrospinal fluid. (31st December 2021) - Ramirez, Christopher E.; Trombetta, Bianca A.; Celia, Amanda M.; LaCasse, Kathryn; Mattingly, Zoe A.; Salloum, Lauren; Orusakwe, Amanze; Esquivel, Rianne N.; Carlyle, Becky C.; Kivisäkk, Pia; Arnold, Steven E.
Abstract: Background: The ATN framework is used to help categorize research subjects as being on the Alzheimer's disease (AD) spectrum. Analytes commonly used in biofluids to determine ATN status were measured across three platforms to examine the reliability of each technology and inter‐platform variability. Method: Cerebrospinal fluid (CSF) samples were obtained from 734 patients undergoing diagnostic lumbar punctures at the MGH Neurology Department. Amyloid β 1–40 (Aβ40), Aβ42, total Tau (tTau), and phosphorylated Tau 181 (pTau 181) were measured in all subjects using EuroImmun ELISA kits on a TECAN FreedomEVO liquid handler. 423 of the subjects also had all four biomarkers measured on a Fujirebio Lumipulse G1200 instrument and 164 had levels of Aβ40 and Aβ42 measured on the Quanterix HD‐X platform. 302 of the subjects had Aβ42, tTau, and pTau 181 quantified by Athena ADmark assays as part of their clinical evaluation. Coefficient of Variations (CVs) were calculated, and data was correlated between platforms to determine inter‐platform variability. Result: The average CV for each analyte was <5% for samples analyzed on the EuroImmun/TECAN platform and <10% on the Fujirebio Lumipulse and Quanterix HD‐X. CVs >20% were not seen in subjects with detectable analyte levels on the EuroImmun/TECAN or Quanterix platforms and the incidence was <5% on the Fujirebio platform. Tight correlations were observed between levels measured on the EuroImmun/TECAN and Fujirebio platforms (R 2 >0.8), while lower correlations were observed between the EuroImmun/TECAN and Quanterix platforms (R 2 =0.4‐0.5 for Aβ40 and Aβ42). The lowest correlation was observed comparing Aβ42 analyzed using EuroImmun/TECAN and Athena ADmark (). ICC values were >0.7 for all analytes compared between EuroImmun/TECAN and Fujirebio platforms. Conclusion: We observed good reliability using all three platforms. to conserve sample. ATN values showed strong correlations between the EuroImmun/TECAN and the Fujirebio platforms and produce . The poor correlation for the Athena ADmark Aβ42 is likely a result of poor control of pre analytical factors in the samples sent for clinical testing and highlights the importance for proper sample handling.